The Future of Education into a Digital World - Jelev, Viorica (Journal of Economic Development, Environment and People, 2015)
The article investigate the role of communication in the digital age, between consumers and business and seeks to render highlighting changes within the Romanian society in the last 26 years, with the effects occurred in people’s behavior, but also the changes of university education at the discipline I teach, Merchandising and International Marketing, with impact on the delivery of new information to the students of the Faculty of Economic Sciences, within Spiru Haret University. We live in an era where everything seems to change and evolve almost overnight. ”The world economic order went through a tectonic transformation, accompanied by, and in part caused by, groundbreaking advances in science and technology and the rise of globalization” . New industries start to develop, while others are on their last legs or already extinct in a world of advanced, emerging, and developing countries. As a result, lots of jobs from years past aren’t as relevant today as they once were, and many no longer exist. Therefore it’s easy to predict that eventually, today’s jobs will evolve into something completely different. And some will become obsolete. And it is those changes that lead to multiple consequences, affecting many other fields, one being education. We need a broad, flexible and motivating education that recognizes the different talents of all children and delivers excellence for everyone. Studying methods and curricula from the 20th century may no longer be relevant in the constantly evolving and changing world of the 21st century, in preparing you for your future job. And in order to maximize your chances of having a successful career in the field of your choice, you have to constantly adapt and evolve. Creative education involves a balance between teaching knowledge and skills, and encouraging innovation. New branches of industries will appear, and potential employers and employees will need to acquire new skills and abilities. And it is these new skills and abilities that should be taught and attained in schools, especially by those attending higher education, which is at an inflection point. It is this constant change, the need to permanently evolve and adapt, that has led to the development of various groups, organizations and networks, tasked with generating answers and solutions to present day problems, as well as predicting future trends in their respective fields of activity. Finally, I try to find the answer to the question "what is the future of humanity?" what typology of man must we form to save the future of the planet. The answer is "the beautiful man", as Dan Puric called in his book.